The Prevalence of Traumatic Brain Injury Among People With Co-Occurring Mental Health and Substance Use Disorders. Issue 3 (May 2017) - McHugo, Gregory J.; Krassenbaum, Sarah; Donley, Sachiko; Corrigan, John D.; Bogner, Jennifer; Drake, Robert E.
Abstract : Objective: To estimate the rate and severity of traumatic brain injury (TBI) among people with co-occurring mental health and substance use disorders and to compare demographic, diagnostic, and institutionalization differences between those who screen positive or negative. Setting: Outpatient community mental health center in Washington, District of Columbia. Participants: A total of 295 people with co-occurring mental health and substance use disorders enrolled in a prospective study of integrated treatment of substance abuse. Design: Cross-sectional baseline assessment. Main Measures: The Ohio State University TBI Identification Method. Standardized measures assessed psychiatric diagnoses, symptom severity, current and lifetime substance use, and history of institutionalization. Results: Eighty percent screened positive for TBI, and 25% reported at least 1 moderate or severe TBI. TBI was associated with current alcohol use and psychiatric symptom severity and with lifetime institutionalization and homelessness. It was more common among participants with posttraumatic stress disorder, borderline personality disorder, and antisocial personality disorder. Men (vs women) and participants with psychotic disorders (vs those with mood disorders) had an earlier age of first TBI with loss of consciousness. Conclusion: TBI is common among people with co-occurring mental health and substance use disorders. Repeated and serious TBIs are common in this population. Failure to detect TBI in people with co-occurring disorders who are seeking integrated treatment could lead to misdiagnosis and inappropriately targeted treatment and rehabilitation.